KEMAMPUAN PEMECAHAN MASALAH DAN SELF EFFICACY MAHASISWA DALAM MENYELESAIKAN WORKSHEET PERSAMAAN DIFERENSIAL TINGKAT SATU DERAJAT N - Rofiroh Rofiroh; Isnaini Mahuda; Taufan Talib; Faqihuddin Faqihuddin (Jurusan Pendidikan MIPA FKIP Universitas Pattimura, 2022)
This study aims to describe the problem solving ability of UMT students in solving the first degree differential equations worksheet with the factorization method. This research is included in the category of qualitative research with a descriptive category. The research subjects were 20 fourth semester students for the 2021/2022 academic year. Data collection methods used are test techniques, filling out structured student worksheets and filling out questionnaires. The test is carried out by filling out the initial test. Filling out structured student worksheets consisting of material, examples and practice questions. Based on the initial test data, filling in the worksheets and questionnaires, the criteria for the three types of students were obtained. Type 1 students fill out 1-2 initial test questions, fill in the material incompletely, the sample questions are only done one question out of the two questions provided with unsystematic problem solving analysis and the last part of the practice questions is not filled in. Type 2 students fill out 2-3 questions for the initial test, complete the material, two examples of questions are done, the practice questions are filled with one question. Type 3 students work on 4 pre-test questions, complete structured student worksheets for each material, sample questions and practice questions. The student fills out a worksheet with a systematic problem-solving analysis